Optical Coherence Tomography–Guided Percutaneous Coronary Intervention in ST-Segment–Elevation Myocardial Infarction: A Prospective Propensity–Matched Cohort of the Thrombectomy Versus Percutaneous Coronary Intervention Alone Trial. (April 2016) - Sheth, Tej N.; Kajander, Olli A.; Lavi, Shahar; Bhindi, Ravinay; Cantor, Warren J.; Cheema, Asim N.; Stankovic, Goran; Niemelä, Kari; Natarajan, Madhu K.; Shestakovska, Olga; Tittarelli, Rachel; Meeks, Brandi; et al.
Abstract : Background—: Patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment–elevation myocardial infarction are at increased risk for adverse events. It is unclear if image guidance by optical coherence tomography (OCT) can improve outcomes in these patients. We compared OCT-guided versus angiography-guided primary PCI for ST-segment–elevation myocardial infarction among patients in the Thrombectomy Versus PCI Alone (TOTAL) trial. Methods and Results—: Among 10 732 patients enrolled in the TOTAL trial, OCT was used for PCI guidance as a part of a prospective substudy in 214 patients. Using 2:1 propensity matching, we identified 428 patients in the trial who had PCI performed with angiography guidance alone. The primary outcome was a composite of cardiovascular death, myocardial infarction, stent thrombosis, and target-vessel revascularization at 1 year. Secondary outcomes included final in-stent angiographic minimum lumen diameter, procedure time, and contrast dose. The final in-stent angiographic minimum lumen diameter was 2.99±0.48 mm in the OCT-guided group versus 2.79±0.47 mm in the angiography-guided group ( P <0.0001). OCT- and angiography-guided PCI had a median (interquartile range) procedure time of 58 (47, 71) minute versus 38 (28, 52) minute ( P <0.0001) and total contrast dose of 239.7±81.1 mL versus 193.3±78.6 mL ( P <0.0001). The primary outcome was observed in 7.5% of the OCT-guided group versus 9.8% of the angiography-guided group (hazard ratio, 0.76; 95% confidence interval, 0.43–1.34; P =0.34). Conclusions—: OCT-guided primary PCI for ST-segment–elevation myocardial infarction was associated with a larger final in-stent minimum lumen diameter. There was no significant difference in clinical outcomes at 1 year; however, the study was underpowered to detect a treatment effect. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01149044. Abstract : Supplemental Digital Content is available in the text.